Structure, Preparation, and Applications of 2D Material‐Based Metal–Semiconductor Heterostructures. Issue 1 (11th January 2021) - Tan, Junyang; Li, Shisheng; Liu, Bilu; Cheng, Hui-Ming
Abstract : Metal–Semiconductor Heterostructures In article number 2000093, Bilu Liu, Hui‐Ming Cheng, and co‐workers highlight recent advances in structure, preparation, and applications of emerging two‐dimensional material‐based metal‐semiconductor heterostructures. Furthermore, the perspectives about the challenges and future research opportunities are given. Such heterostructures are suggested as promising candidates in 2D integrated electronics and high‐performance energy‐related devices.